Developmental and metabolic plasticity of white-skinned grape berries in response to Botrytis cinerea during noble rot - Blanco Ulate, Barbara (2015)
Noble rot results from exceptional infections of ripe grape (Vitis vinifera) berries by Botrytis cinerea. Unlike bunch rot, noble rot promotes favorable changes in grape berries and the accumulation of secondary metabolites that enhance wine grape composition. Noble rot-infected berries of cv Sémillon, a white-skinned variety, were collected over 3 years from a commercial vineyard at the same time that fruit were harvested for botrytized wine production. Using an integrated transcriptomics and metabolomics approach, we demonstrate that noble rot alters the metabolism of cv Sémillon berries by inducing biotic and abiotic stress responses as well as ripening processes. During noble rot, B. cinerea induced the expression of key regulators of ripening-associated pathways, some of which are distinctive to the normal ripening of red-skinned cultivars. Enhancement of phenylpropanoid metabolism, characterized by a restricted flux in white-skinned berries, was a common outcome of noble rot and red-skinned berry ripening. Transcript and metabolite analyses together with enzymatic assays determined that the biosynthesis of anthocyanins is a consistent hallmark of noble rot in cv Sémillon berries. The biosynthesis of terpenes and fatty acid aroma precursors also increased during noble rot. We finally characterized the impact of noble rot in botrytized wines. Altogether, the results of this work demonstrated that noble rot causes a major reprogramming of berry development and metabolism. This desirable interaction between a fruit and a fungus stimulates pathways otherwise inactive in white-skinned berries, leading to a greater accumulation of compounds involved in the unique flavor and aroma of botrytized wines.